Василь Стус як митець, що боровся за національне відродження України - Чучко, О. О.; Бадєєва, Л. І. (ХНУРЕ, 2020)
In this article I am trying to describe the impact that Vasyl Stus had on the national revival of Ukraine, value of his hard work and the heritage that he has left for Ukrainians across generations. He is the man to look up to for the people of Ukraine in the time of national crisis. The effort that he has put into resurrecting a national spirit cannot be undervalued. It could be even said that his work is one of the reasons that Ukraine is independent today. That’s why I chose to examine and explore his biography, works, other scientists’ studies on the matter. I want Ukrainians to be aware who they should be thankful to.
Keywords: українська державність; українознавство